Theoretical study of characteristics and mathematical model of convective drying of foods - Saparov Dj.E.; Sultonova S.A.; Guven E.С.; Samandarov D.I.; Rakhimov A.M. (E3S Web of Conferences, 2023)
The characteristics of convective drying of potatoes at different temperatures, air velocity and slice thickness are investigated and a mathematical model is developed. The results show that the drying time decreases with increasing drying temperature. Compared with air velocity, drying temperature and slice thickness have a greater influence on the drying rate, and the period of velocity drop is the main stage of the convective drying process. As a model for convective drying of potato, the equations for 6 drying models are fitted and the optimal model is selected.